2005
DOI: 10.1111/j.1523-5378.2005.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori Infection

Abstract: A large number of studies on diagnostic tests have been published this year. New tests were proposed for the detection of Helicobacter pylori antigens in stools and new molecular methods (real-time polymerase chain reaction) to look for antimicrobial susceptibility. The other standard tests have been applied in different situations to improve the diagnosis of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 77 publications
2
33
1
2
Order By: Relevance
“…Heterogeneous results have been reported concerning the performance of the rapid ImmunoCard STAT! HpSA test in pretreatment versus posttreatment patients (1,7,9). The difference could also be due to the higher percentage of males (70%) than females (30%) than in our investigation (49% and 51%, respectively).…”
contrasting
confidence: 42%
See 3 more Smart Citations
“…Heterogeneous results have been reported concerning the performance of the rapid ImmunoCard STAT! HpSA test in pretreatment versus posttreatment patients (1,7,9). The difference could also be due to the higher percentage of males (70%) than females (30%) than in our investigation (49% and 51%, respectively).…”
contrasting
confidence: 42%
“…While the value of enzyme immunoassays (EIAs) using either polyclonal or monoclonal antibodies is well documented, the sporadic existing data for the first developed and commercially available rapid test (ImmunoCard STAT! HpSA) showed enormous differences among the studies (1,7,8,14,17), and its reliability is reported to be somewhat lower than that of monoclonal fecal antigen EIA (2,9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, stool PCR may be considered as better test than HpSA because the HpSA test shows heterogeneity in the sensitivity rates that ranged from 58% to 96% and specificity ranged from 67% to96 % [14][15][16][17][18][19][20][21][22]. This is because of the difficulty in obtaining polyclonal antibodies of constant quality [23].…”
Section: Discussionmentioning
confidence: 99%